2002
DOI: 10.1099/0022-1317-51-4-295
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 induction and adhesion of the coccoid form of Helicobacter pylori

Abstract: To determine the pathological significance of the coccoid form of Helicobacter pylori, its adhesion to and induction of secretion of interleukin-8 (IL-8) by gastric epithelial (MKN45) cells were studied. By flow cytometry, the adhesion of the coccoid form to MKN45 cells was significantly lower than that of the helical form. The monoclonal antibody A20 recognising lipopolysaccharide of H. pylori inhibited the adhesion of the coccoid form to MKN45 cells as much as that of the helical form. There was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…As the known interaction of DFMO with host cells prevents discrimination of the effect of DFMO on bacteria in the stomach we performed in vitro experiments using the human gastric AGS cell line in the absence of DFMO in the cocultures and observed that IL-8 expression was significantly reduced. Some studies using coccoid-form bacteria have reported that they induce lower levels of IL-8 in epithelial cells, and, concomitantly, adhere to a lesser degree than helical H. pylori [44], [45]. Our data indicate no loss of adherence of DFMO-treated bacteria, suggesting that other alterations of bacterial physiology are responsible for the reduction in IL-8 expression.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As the known interaction of DFMO with host cells prevents discrimination of the effect of DFMO on bacteria in the stomach we performed in vitro experiments using the human gastric AGS cell line in the absence of DFMO in the cocultures and observed that IL-8 expression was significantly reduced. Some studies using coccoid-form bacteria have reported that they induce lower levels of IL-8 in epithelial cells, and, concomitantly, adhere to a lesser degree than helical H. pylori [44], [45]. Our data indicate no loss of adherence of DFMO-treated bacteria, suggesting that other alterations of bacterial physiology are responsible for the reduction in IL-8 expression.…”
Section: Discussionsupporting
confidence: 56%
“…Some studies have reported that coccoid-form H. pylori exhibit reduced adherence compared to helical-shaped bacteria and that this correlates with lesser induction of IL-8 [44], [45]. To determine if a similar effect occurred with the bacteria altered by DFMO, we compared adherence to AGS cells of H. pylori grown with or without 1% DFMO for 12 h. There was not a decrease, but rather there was a modest increase in adherence, with 1.01±0.22% of untreated bacteria and 1.75±0.33% of DFMO-treated bacteria found to be adherent, respectively (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…4A). Cole et al (1997) and Osaki et al (2002) have shown that coccoid H. pylori have a reduced ability to induce IL-8 secretion compared with spiral H. pylori in AGS and KATO cells. The present study has also shown that the geneexpression level of IL-8 in GES-1 cells infected with coccoid H. pylori is lower than that of cells infected with spiral H. pylori.…”
Section: Adhesion Of Spiral and Coccoid H Pylori To Ges-1 Cellsmentioning
confidence: 99%
“…Coccoid H. pylori is characterized by low virulence (including changes in cell adhesion, urease enzyme activity, cellular vacuolating cytotoxin, etc.) and a weak inflammatory response; therefore, it cannot be removed easily . H. pylori that presents in gastric cancer is usually in the coccoid form, and the coccoid H. pylori detection rate in gastric cancer tissue is significantly higher than that of in ulceration .…”
Section: Introductionmentioning
confidence: 99%